Pendidikan Islam Abad 21: Antara Tuntutan Komodifikasi & Nilai Religius - Nurohmat Nurohmat; Cecep Sumarna; Abdul Rozak (Peneliti.net, 2023)
In the midst of efforts to provide quality Islamic education services to the user community, it certainly has an impact on the need for an adequate budget, including the supply of budget from the user community, giving rise to the stigma of 'commodification' of Islamic education. On the other hand, paradigmatically, Islamic education is demanded with humanist, religious, and sacred values that are perceived as far from the commodification and capitalization of education. This study aims to examine conceptually the commodification of Islamic education and the demands of maintaining the substance of religious values in 21st century Islamic education. Methods The research used in this research is literature review or literature review in the form of scientific articles contained in journals and books related to the research theme. The results of the study indicate that there is a new paradigm in Islamic education that demands the process of commodification of Islamic education. On the other hand, Islamic education seeks to dialogue between the sources of Islamic teachings and the demands of the times and human needs. Religious values exist as an adhesive for the peace of students in meeting the demands of the times. So that paradigmatically there is a need for reconciliation between commodification demands and religious substance in Islamic education.